Depresión y su incidencia en las relaciones interpersonales de un joven de 25 años del cantón Ventanas - Flores Vargas, Kevin Anthony (2022)
The topic "Depression and its impact on interpersonal relationships in a 25-year-old from the Ventanas canton", because the first is based on a psychological alteration of the state of mind, which has as characteristic symptoms persistent sadness, a low level of self-esteem, disinterest and a decrease in the functions at the psychic level of the individual, while interpersonal relationships constitute links or bonds that are established between the members of a community, which are important for the integral development of people. In the case study, a qualitative methodology was used, through a descriptive approach and a quasi-experimental design, by applying the techniques of clinical observation, unstructured interview, clinical history and battery of psychometric tests, such as: Beck Depression Inventory, Zung Self-Assessment Scale for Depression (SDS), Rosenberg Self-Esteem Scale (RSE). The presumptive psychodiagnosis obtained was Persistent depressive disorder (dysthymia) 300.4 (F34.1) according to DSM-5. Among the outstanding findings are the incidence of depression in the relationships that the subject has to socialize in their environment. It is necessary to propose various psychotherapeutic techniques with the approach of cognitive behavioral therapy.